Green sukuk issuance: a case study of public university in Malaysia - Muhamat, Amirul Afif; Nizar, Nurhuda; Senawi, Azhan Rashid; Abdul Karim, Norzitah; Kassim, Salina; Ismail, Heazar (UMT Press, 2024)
Universiti Teknologi MARA (UiTM) is one of Malaysia’s premier public universities, offering a wide range of courses, from pre-diploma to postgraduate studies. In addition to its educational services, the university engages in commercial activities through its investment arm, UiTM Holdings Sdn. Bhd. One of its subsidiaries, UiTM Energy and Facilities has ventured into the solar power sector, which is managed by UiTM Solar Power Sdn. Bhd. (USPSB). To finance its operations, USPSB has issued green sukuk. This paper aims to investigate the factors driving USPSB’s entry into the green industry and examines the challenges it faces as a university-owned company with no prior experience in solar projects. The study utilised a single descriptive case study design and included semi-structured interviews with experts in the field. The findings revealed five push factors and two pull factors that influenced USPSB’s decision to enter the sector, as well as the primary motivations for issuing sukuk instead of other debt instruments. The study highlighted the issues and challenges USPSB encountered in dealing with green sukuk and provided recommendations to enhance the attractiveness of sustainable and responsible investment sukuk for investors, issuers, and regulators.